Winning the war against COVID-19 in Malaysia: An achievable goal? - Jaafar H.; Azzeri A. (Malaysian Public Health Physicians Association, 2024)
Malaysian Journal of Public Health Medicine 2020, Vol. 20 (1): 148-149